Corporate social responsability: Selected theoretical and empirical aspects - Janina Witkowska (Comparative Economic Research. Central and Eastern Europe, 2016)
The notion of Corporate social responsibility (CSR) is still stirring debate over how it should be interpreted, what models of CSR dominate in business practice, and consequences of enterprises' engagement into socially responsible actions. While business practice demonstrates that companies voluntarily include social and environmental issues into their activities and into their relations with stakeholders, it is hard to determine what intentions motivate them to do so. This paper analyses selected aspects of discussions focused on the notion of CSR and identifies controversies over the standardisation of ethical and social business activities.
Keywords: 330; corporate social responsibility; CSR models; standards of ethical and social business conduct